Paracrine IL-6 signaling mediates the effects of pancreatic stellate cells on epithelial-mesenchymal transition via Stat3/Nrf2 pathway in pancreatic cancer cells - Wu, Yuan Seng; Chung, Ivy; Wong, Won Fen; Masamune, Atsushi; Sim, Maw Shin; Looi, Chung Yeng (Biochimica et biophysica acta. General subjects, 2017)
We previously showed that pancreatic stellate cells (PSC) secreted interleukin (IL)-6 and promoted pancreatic ductal adenocarcinoma (PDAC) cell proliferation via nuclear factor erythroid 2 (Nrf2)-mediated metabolic reprogramming. Epithelial-mesenchymal transition (EMT) is a key process for the metastatic cascade. To study the mechanism of PDAC progression to metastasis, we investigated the role of PSC-secreted IL-6 in activating EMT and the involvement of Nrf2 in this process. Gene expression of IL-6 and IL-6Rα in PSC and PDAC cells was measured with qRT-PCR. The role of PSC-secreted IL-6, JAK/Stat3 signaling, and Nrf2 mediation on EMT-related genes expression was also examined with qRT-PCR. EMT phenotypes were assessed with morphological change, wound healing, migration, and invasion. PSC expressed higher mRNA levels of IL-6 but lower IL-6Rα compared to PDAC cells. Neutralizing IL-6 in PSC secretion reduced mesenchymal-like morphology, migration and invasion capacity, and mesenchymal-like gene expression of N-cadherin, vimentin, fibronectin, collagen I, Sip1, Snail, Slug, and Twist2. Inhibition of JAK/Stat3 signaling induced by IL-6 repressed EMT and Nrf2 gene expression. Induction of Nrf2 activity by tert-butylhydroquinone (tBHQ) increased both EMT phenotypes and gene expression (N-cadherin, fibronectin, Twist2, Snail, and Slug) repressed by IL-6 neutralizing antibody. Simultaneous inhibition of Nrf2 expression with siRNA and Stat3 signaling further repressed EMT gene expression, indicating that Stat3/Nrf2 pathway mediates EMT induced by IL-6. IL-6 from PSC promotes EMT in PDAC cells via Stat3/Nrf2 pathway. Targeting Stat3/Nrf2 pathway activated by PSC-secreted IL-6 may provide a novel therapeutic option to improve the prognosis of PDAC. •PSC-derived IL-6 promotes EMT phenotypes and gene expression in Panc-1 cells.•JAK/Stat3 signaling induced by IL-6 mediates EMT and Nrf2 gene expression.•Intracellular Nrf2 activity is essential for EMT phenotypes and gene expression.•Simultaneous inhibition of Nrf2 and Stat3 signaling represses EMT gene expression.•Targeting Stat3/Nrf2 pathway downstream of IL-6 may improve PDAC prognosis.